Profit Sharing Dalam Program Water Supply Pada Badan Usaha Milik Desa Pandan Harum Desa Selat - Kadek Feri Perdana Putra; Nyoman Ari Surya Darmawan (Universitas Pendidikan Ganesha, 2022)
This study aims to determine how the application of a profit sharing system in the water supply program at the BUMDes Pandan Harum, Selat Village. The formulation of the problem in this study is